Vergi hukukunda zamanaşımı - Karagöz, Berkan (My University, 2008)
Vergi hukukunda zamanaşımı, vergi borcunu sona erdiren nedenlerden biridir. Zamanaşımıyla, vergi yasalarında öngörülen zamanın geçmesiyle ve şartların oluşmasıyla devletin vergi alacağını talep etme hakkı ortadan kalkmaktadır. Vergi hukukunda zamanaşımına başvurulmasının hukuki nedenleri, kamu yararı ve objektif iyiniyet kuralıdır. Söz konusu kurumun, anayasal dayanakları ise Anayasa’nın 2. maddesinde yer alan hukuk devleti ilkesi ve 73. maddesinde yer alan vergilendirme ilkeleridir. Hukuk devleti ilkesi, devletin vergi alacağının zaman bakımından sınırlandırılmasını gerektirir. Anayasa’nın 73 maddesinde yer alan vergide yasallık ilkesi açısından zamanaşımı, verginin kurucu öğelerinden biridir. Bu yüzden vergi yasalarında açıkça düzenlenmesi gerekir. Öte yandan, kamu yararı üzerine yükselen zamanaşımı kurumunda eşitsizlikten bahsedilemez. Ölçülülük ilkesi gereği, vergi yükümlüsü lehine olmayan zamanaşımı kurumu vergi hukukunda bir anlam ifade etmez. Ölçülülük ilkesi açısından, vergi bilincinin ve vergi ahlakının geliştiği bir ülkede zamanaşımı sürelerinin yükümlü aleyhine olması ve görece daha uzun olması beklenemez. Diğer yandan, vergi hukukunda zamanaşımı ile, vergilendirmeyle yükümlünün mülkiyet hakkına yapılan müdahalenin sınırı, zaman bakımından çerçevelenir ve yükümlüye hukuksal güvence sağlanır. Çalışma beş bölümden oluşmaktadır. Birinci bölümde zamanaşımı kavramı genel olarak incelenerek, ikinci bölümde vergi hukukunda zamanaşımının tarihçesi ve kaynakları ele alınmıştır. Tezin üçüncü bölümünde ise vergi hukukunda zamanaşımının anayasal dayanaklarının ve hukuki niteliğinin ne olduğu ortaya konulmaya çalışılmıştır. Tezin devam eden bölümlerinde uygulama üzerinde durulmuştur: Dördüncü bölümde vergi aslı bakımından zamanaşımı türlerinden Vergi Usul Kanunu’nda düzenlenen tarh zamanaşımı birinci altbölümde, AATUHK’nda düzenlenen tahsil zamanaşımı ikinci altbölümde incelenmiştir. Beşinci bölümde ise vergi cezaları bakımından uygulanan zamanaşımı hükümleri değerlendirilmiştir. Ayrıca çalışmada, Anayasa Mahkemesi ve Danıştay kararlarından da yararlanılmıştır. Vergi Hukuku, Zamanaşımı, Vergilendirme, Vergi Borcunun Sona Ermesi.

The theme of the thesis is the prescription in tax law. In taw law, the prescription is one of the reasons for the termination of tax debts. By the prescription applies, when the stipulated time lapses and the specified conditions occur, the claims for the tax receivable by the government are erased. In tax law, legal cause for application for the prescription is on the common wale. For the legal foundation in questions, the constitutional basics are the principle of the rule of law contained in Section 2 of the Constitution and the principles of taxation contained in Section 73. The principle of the rule of law require that a time limitation be placed on the government’s tax receivable. In terms of the legality principle at taxation in Section 73, the prescription is one of the constituent of a taxation law. For this reason, it must be clearly drafted in tax law. On the other side, inequality cannot be mentioned in the formation of the prescription for the benefit of the tax administration. As required by the proportionality principle, the prescription not in favor of the tax payer have no meaning. In terms of the proportionality principle, in a country where the tax consciousness and the taxation ethics are being developed, it cannot be expected that the prescription be against the taxpayer and relatively longer. On the other hand, with the prescription in tax law, the limit of the intervention to the property rights of the taxpayer is circumscribed in point of a time and also a time framework is applied to give taxpayer legal assurance. This thesis is consisted of five sections. In the first section, the prescription concept is examined in general. In the second section, the history and sources of the prescription in tax law are studied. In the third section of this thesis, the constitutional basics of the prescription in tax law and what the legal aspects and results of the prescription is has tried to be considered. The latter part of the thesis is focused on the practice. Accordingly in the first subsection of the fourth section, the prescription about assessment contained in the Tax Procedure Code numbered 213 has been analyzed. Afterwards, the prescription about the collection of public receivables contained in the Code About the Collection Procedures for the Public Receivables numbered 6183 has been analyzed under second subsection of the fourth section. In the fifth section, the prescription laws’ have been evaluated in terms of the tax penalties. Furthermore this thesis has referenced the Constitutional Courts and the Council of state decisions. Key Words: Tax Law, the prescription, taxation, the termination of tax debts.
Keywords: Hukuk; Mali Hukuk; Vergi Hukuku; Vergilendirme